Assessing parent interaction with deaf infants: A quantitative survey of UK professional practice - Curtin, Martina; Morgan, Gary; Cruice, Madeline; Herman, Rosalind (International journal of language & communication disorders, 2023)
Background Between 90% and 95% of deaf children are born to hearing parents who often need support with how to adapt their communication. Parent–child interaction (PCI) is an important predictor of deaf children's future language development. It is therefore necessary for professionals to assess parents’ strengths and needs to identify areas for intervention. Qualified teachers of the deaf (QToDs), speech and language therapists (SLTs), psychologists, and national deaf child and adolescent mental health (NDCAMHS) professionals regularly support families with deaf children. With no current evidence‐based tool available to assist with the assessment of PCI in deafness, it is important to gather information on current professional practice as this may differ from known practices within research. Aims To survey the practices of UK‐based professionals in the assessment of PCI where the deaf infant is aged 0–3 years. Professionals were QToDs, SLTs, psychologists or psychiatrists and professionals working at NDCAMHS services. Methods & Procedures After a pilot phase, an 85‐item survey was distributed electronically through a range of professional and social media networks. Survey items were based on a systematic review of PCI with deaf infants. Survey questions were focused on parent behaviours that were assessed, methods of assessment, goal planning and service provision. Analysis was conducted using descriptive and inferential statistics. Outcomes & Results A total of 190 professionals from across the UK completed part 1 of the survey; this decreased to 148 in part 4. Respondents were primarily female, hearing, used spoken English and had 16 years or more experience. Results indicate that PCI is routinely assessed by a large proportion of professionals and there is a substantial overlap in which parent behaviours are assessed. Some parent behaviours are assessed that do not feature in the research. Methods of assessment are informal and predominantly consist of observation and note making, with professionals using their own skills and experience to analyse interaction. Goal setting practices were largely similar between professionals, with many jointly deciding goals with parents. Conclusions & Implications This survey highlights the range of parent behaviours assessed by UK professionals in PCI with deaf children aged 0–3. This survey provides valuable information about and for professionals who assess PCI and set intervention goals with parents. Information from research and professional practice is important to consider in the design of a future PCI assessment. Implications are included for future research in this area. What This Paper Adds What is already known on this subject Parental involvement is one of the greatest predictors of deaf children's language outcomes. With many deaf children born to hearing parents, parents often need guidance with how to facilitate effective communication. A recent systematic review identified the range of parent behaviours and methods used to analyse PCI in international research studies, but little evidence or guidance exists on how professionals assess this phenomenon in practice. What this study adds This is the first survey to generate large, valuable practice‐based evidence for the assessment of parents’ communication behaviours as they interact with their deaf infants aged 0–3. The survey recruited a range of multidisciplinary professionals working on interaction within this field: SLTs, qualified teachers of the deaf, psychologists or psychiatrists, and professionals working within deaf child and adolescent mental health services. The study reports on which behaviours these professionals assess and how, and includes information on the goal setting behaviours of practitioners. Most respondents were highly experienced; the survey, therefore, reveals expert practice within the field. What are the potential or actual clinical implications of this work? We recommend the following practice: (1) incorporate a range of parent‐based behaviours in PCI assessments, including establishing joint engagement and parental sensitivity, as well as communication‐focused behaviours; (2) video record PCI assessments where possible to enable professionals and parents to watch and reflect together; (3) following assessment, set parent‐focused goals in collaboration with families, ensuring parents’ skills, particularly their strengths, are considered. All primary caregivers should be included in the process where possible; and (4) reassess PCI regularly (at least termly) to monitor and encourage families’ progress. The timing of reviews should be discussed between parent and professional.